Brak – podarok klassovomu vragu - Korshunov, Nikolai Elizarovich (ОГИЗ - ИЗОГИЗ (Izogiz), 1933)
A worker cutting a piece of board, with a signpost and a raven behind him Original title: Брак – подарок классовому врагу. Suggested translation: Spoilage is a gift to the class enemy PO-0022